A clinically feasible algorithm for the parallel detection of glioma‐associated copy number variation markers based on shallow whole genome sequencing - Shuai Wu; Chenyu Ma; Jiawei Cai; Chenkang Yang; Xiaojia Liu; Chen Luo; Jingyi Yang; Zhang Xiong; Dandan Cao; Hong Chen (Wiley, 2024)
Abstract Molecular features are incorporated into the integrated diagnostic system for adult diffuse gliomas. Of these, copy number variation (CNV) markers, including both arm‐level (1p/19q codeletion, +7/−10 signature) and gene‐level (EGFR gene amplification, CDKN2A/B homozygous deletion) changes, have revolutionized the diagnostic paradigm by updating the subtyping and grading schemes. Shallow whole genome sequencing (sWGS) has been widely used for CNV detection due to its cost‐effectiveness and versatility. However, the parallel detection of glioma‐associated CNV markers using sWGS has not been optimized in a clinical setting. Herein, we established a model‐based approach to classify the CNV status of glioma‐associated diagnostic markers with a single test. To enhance its clinical utility, we carried out hypothesis testing model‐based analysis through the estimation of copy ratio fluctuation level, which was implemented individually and independently and, thus, avoided the necessity for normal controls. Besides, the customization of required minimal tumor fraction (TF) was evaluated and recommended for each glioma‐associated marker to ensure robust classification. As a result, with 1× sequencing depth and 0.05 TF, arm‐level CNVs could be reliably detected with at least 99.5% sensitivity and specificity. For EGFR gene amplification and CDKN2A/B homozygous deletion, the corresponding TF limits were 0.15 and 0.45 to ensure the evaluation metrics were both higher than 97%. Furthermore, we applied the algorithm to an independent glioma cohort and observed the expected sample distribution and prognostic stratification patterns. In conclusion, we provide a clinically applicable algorithm to classify the CNV status of glioma‐associated markers in parallel.